2B or not 2B? A diagnosis of von Willebrand disease a lifetime of 86 years in the making. Issue 3 (April 2021) - Chapman, Kent; Prasad, Ritam; Mohammed, Soma; Favaloro, Emmanuel J.
Abstract : N/A: Type 2B von Willebrand disease (2B VWD) is a rare, autosomal dominant bleeding disorder characterized by a hyperadhesive form of von Willebrand factor (VWF). 2B VWD expresses phenotypically as an enhanced ristocetin-induced platelet aggregation and usually also a discordance in VWF activity versus protein level, with loss of high molecular weight VWF and (mild) thrombocytopenia. While all cases of 2B VWD supposedly share these characteristics, there is significant heterogeneity in laboratory findings within this group of patients, which are largely dictated by the underlying genetic defect. We present a case of such a patient, expressing a clearly atypical VWF phenotype, but as still associated with enhanced ristocetin-induced platelet aggregation, thrombocytopenia, and a previously undescribed VWF variant (c.4130C>G; p.Ala1377Gly). The patient was misdiagnosed over his lifetime as idiotypic thrombocytopenia – a (mis)diagnosis that took a lifetime of 86 years to redress.